Developing a Green Lost Circulation Material (LCM) Derived From Coconut Coir Waste - Jamaludin, Izzuddin (Universiti Teknologi Petronas, 2011)
This dissertation presents a project aims to avoid or significantly reduce lost circulation of drilling fluid during drilling operation by introducing coconut coir waste as a lost circulation material (LCM). The oil and gas industry spends millions of dollars a year to combat lost circulation and the detrimental effects it propagates, such as loss of rig time, stuck pipe, side-tracks, blowouts and, occasionally, the abandonment of expensive wells. It is estimated that lost circulation costs the industry about US $800 million per year, while the lost circulation products could represent as much as US $200 million. The objectives of this research will be focusing on formulating and developing a composition of drilling fluid containing coconut (Cocos Nucifera) coir as a lost circulation material (LCM) to either prevent or mitigate loss of drilling fluid during drilling wells. Two cases were developed in order to examine coconut coir feasibility as LCM by comparing with industrial nut plug and corn cob and to study on the effect of coconut coir concentration and particle size towards mud rheology, filtration volume and filter cake thickness. Coconut coir is being examined as it is among the easiest fruit peel waste that can be found in the country and based on its characteristics. Based on study, coconut palm is one of the most important crops in Malaysia. With the increased of total area planted from 117000 hectares in 1998 to 147000 hectares in 2004, it also indicates that the fruits' wastes are increasing aunually. The high content of lignin in coconut coir made the fiber tougher and stiffer as compared to other fibrous wastes. Overall, coconut coir has showed some potential in acting as LCM. Although nut plug illustrated convincing values of plastic viscosity, yield point and gel strength, coconut coir has the advantages over the amount of filtrate and mud cake thickness. For the effect of particle size and concentration, course particles demonstrated good plastic viscosity and yield point. Finer particles, on the other hand, managed to control fluid loss better than course particles with thinner mud cake formation.